Synthesis and Biological Study of 4-Aminopyridine-Peptide Derivatives Designed for the Treatment of Neurodegenerative Disorders - Vezenkov, Lyubomir T.; Tsekova, Daniela S.; Kostadinova, Ivanka; Mihaylova, Rositsa; Lozanov, Valentin; Vassilev, Nikolay G.; Danchev, Nikolai; Tsakovska, Ivanka; Pajeva, Ilza (Current Alzheimer Research, 2023)
Background: Alzheimer’s disease (AD) and Multiple sclerosis (MS) lead to neurodegenerative processes negatively affecting millions of people worldwide. Their treatment is still difficult and practically incomplete. One of the most commonly used drugs against these neurodegenerative diseases is 4-aminopyridine. However, its use is confined by the high toxicity. Objectives: The aim of this work is to obtain new peptide derivatives of 4-aminopyridine with decreased toxicity compared to 4-aminopyridine. Methods: Synthesis was conducted in solution using a consecutive condensation approach. The new derivatives were characterized by melting points, NMR, and Mass spectra. Important ADME (absorption, distribution, metabolism, and excretion) properties have been studied in silico using ACD/Percepta v.2020.2.0 software. Acute toxicity was determined in mice according to a Standard protocol. All new derivatives were tested in vitro for cytotoxic activity in a panel of human (HEP-G2, BV-173) and murine (NEURO 2A) tumor cell lines via a standard MTT-based colorimetric method. β-secretase inhibitory activity was determined by applying the fluorescent method. Results: New derivatives of 4-aminopyridine containing analogues of the β-secretase inhibitory peptide (Boc-Val-Asn-Leu-Ala-OH) were obtained. The in vivo toxicity of the tested compounds was found to be as high as 1500 mg/kg. Cell toxicity screening against tumor cell lines of different origins showed negligible growth-inhibitory effects of all investigated 4-aminopyridine analogues. Conclusion: Synthesis of new peptide derivatives of 4-aminopyridine is reported. Acute toxicity studies revealed a ca. 150 times lower toxicity of the new compounds as compared to 4-aminopyridine that may be ascribed to their peptide fragment.
Keywords: cytotoxicity